2019
DOI: 10.1111/hae.13870
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and management of the haemophilia‐associated pseudotumours

Abstract: | INTRODUC TI ONHaemophilia-associated pseudotumours (HPT) were first described by Starker in 1918 and are a continuing cause of severe morbidity and mortality for patients with congenital haemophilia. 1 The prevalence of HPT has been described between 1% and 2% of patients with haemophilia with similar levels persisting despite the use of recombinant factor replacement over the last decades. 2,3 The clinical course of HPT can be heterogenous due to a variety of factors including age of onset, disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…With regard to the most frequent locations in total HPT patients, our finding agrees with Zhai's 26 on the top two locations: thigh and ilium. A review including 134 described HPTs by Doyle et al also showed the same result 33 . One author 26 pointed out that HPT had occurred outside a joint, but we found two cases around the knee.…”
Section: Discussionsupporting
confidence: 81%
“…With regard to the most frequent locations in total HPT patients, our finding agrees with Zhai's 26 on the top two locations: thigh and ilium. A review including 134 described HPTs by Doyle et al also showed the same result 33 . One author 26 pointed out that HPT had occurred outside a joint, but we found two cases around the knee.…”
Section: Discussionsupporting
confidence: 81%
“…HPTs are classified into 3 types according to the imaging features and location: soft tissue, subperiosteal, and intraosseous types [6]. HPTs normally involve adjacent bone and result in massive bone destruction [7].…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons may encounter many challenges during surgery, such as abnormal anatomy, multiple fixation options, and bone reconstruction considerations. Complications, including nonunion, infection, fixation failure, inhibitor development, and pseudotumor recurrence, should not be ignored because they exert a profound influence on patient outcomes [7,12]. Avoiding complications is challenging for surgeons, and sometimes these complications are difficult to resolve.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, according to the imaging features and location of HPTs, they can be classi ed into 3 types: soft-tissue, subperiosteal and intraosseous types [6]. HPTs will normally involve adjacent bone, result in massive bone destruction [7].…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons may encounter many challenges during operation, such as abnormal anatomy and multiple xation options and bone reconstruction programs. In addition, complications including nonunion, infection, xation failure, inhibitor development and pseudotumor recurrence should not be ignored, as they exert a profound in uence on patient outcomes [7,12]. Due to the rarity of these fractures, reports of surgical treatment for patients with HPT-related femoral fractures are scarce.…”
Section: Introductionmentioning
confidence: 99%